Two new species of the genus Glyptotendipes Kieffer (Diptera: Chironomidae: Chironominae) from West Bengal India. (3rd July 2021) - Konar, Sanghamitra; Majumdar, Uttaran
ABSTRACT: Two new species belonging to the nominal subgenus of Glyptotendipes Kieffer are described in this paper. Glyptotendipes ( G .) hebetare sp. nov . is described on the basis of adult male, pupa and larva and G . ( G .) inflatum sp. nov . is described on the basis of adult male and pupa. A key to adult males of the Oriental species of the Glyptotendipes is also provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:6B83A8C2-F7B0-4768-9ADB-8B89C60B81EB